Pola Pembinaan Perilaku Remaja Dalam Meningkatkan Akhlak - Ridwan, Muhammad (Center for Religious Studies and Social Empowerment Foundation, 2022)
This article wants to discuss the understanding and implementation of patterns of fostering adolescent behavior in improving morals in the Buluran Kenali Village, Jambi City. The focus of the study in this article is how is the understanding of parents regarding the pattern of fostering adolescent behavior in improving morals in the Buluran Kenali Village, Jambi City? This research is a qualitative research with a phenomenological approach. The research findings show that parents' understanding of the patterns of adolescent behavior development in the Buluran Kenali Village, Jambi City is still low. Guidance on the behavior of adolescents in the Buluran Village, Know the City of Jambi, occurs a lot in social-religious activities in the community. This is because parents do not have enough time to spend with their children due to busy work outside the home, lack of knowledge about educating children about religion, association of children in the environment and understanding and awareness of the children themselves which are not optimal. Therefore, active involvement in managing mosque youth organizations, being actively involved in religious activities, as well as being involved in managing mosques, are all important coaching for youth. Artikel ini hendak membahas tentang pemahaman dan pelaksanaan pola pembinaan perilaku remaja dalam meningkatkan akhlak di Kelurahan Buluran Kenali Kota Jambi. Fokus kajian dalam artikel ini adalah bagaimana pemahaman orang tua mengenai pola pembinaan perilaku remaja dalam meningkatkan akhlak di Kelurahan Buluran Kenali Kota Jambi? Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi. Temuan penelitian menunjukkan bahwa pemahaman orang tua mengenai pola pembinaan perilaku remaja di Kelurahan Buluran Kenali Kota Jambi masih rendah. Pembinaan perilaku remaja Kelurahan Buluran Kenali Kota Jambi, banyak terjadi dalam kegiatan sosial keagamaan di masyarakat. Hal itu karena orang tua kurang memiliki waktu bersama anak akibat kesibukan pekerjaan di luar rumah, kurangnya pengetahuan mendidik anak tentang agama, pergaulan anak dalam lingkungan dan pemahaman dan kesadaran anak itu sendiri yang belum maksimal. Oleh karenanya, keterlibatan secara aktif dalam mengurus organisasi remaja Masjid, terlibat secara aktif dalam kegiatan keagamaan, serta keterlibatan dalam pengurusan masjid, kesemuanya merupakan pembinaan penting bagi remaja.